Lessons from Environmental Mainstreaming : Towards Environmental Sustainability - Tlaiye, Laura; Awe, Yewande (Washington, DC, 2013)
The paper, Lessons from Environmental Mainstreaming: Towards Environmental Sustainability was completed December 2010. The core message of the 2001 World Bank Environment Strategy was to support developing countries in their efforts to mainstream or integrate environmental considerations into activities of the economic sectors (energy, water supply, urban development, rural development, transport, etc.). The Strategy sought to move beyond mitigating environmental impacts of development, embodied in the Bank s environmental safeguards policies, towards a progressive adoption of environmental aspects across Bank services. The tools suggested to help the Bank s client countries achieve such integration were upstream analytical and advisory inputs for sector decision-making and for improving the understanding of poverty-environment linkages. As an input to the new 2010 World Bank Environment Strategy, this paper aims at assessing the degree of mainstreaming environmental activities in Bank activities, reviewing how this was achieved, and determining whether it helped countries in their environmental management efforts. Furthermore, since the 2010 Environment Strategy seeks to move the World Bank Group towards environmental sustainability, the paper recommends illustrations of environmental outcome indicators as part of the 2010 Strategy's results framework.